Two new species of Ribes (Grossulariaceae) from Peru - Weigend, Maximilian (2023)
The genus Ribes (Grossulariaceae) has a center of diversity in the tropical Andes, especially in Peru. Several new species have been discovered in recent years and additional collections keep turning up material of undescribed species. In the present study we describe two additional new species, both from the wide-ranging species complex around Ribes andicola. Ribes lambayequensis comes from a known centre of diversity of the Andean plants, the Amotape-Huancabamba Zone, but represents the first species of the genus from Lambayeque. It differs most obviously from its geographical neighbor Ribes colandina by its two-coloured flowers in erect inflorescences (versus uniformly dark red flowers in pendulous racemes in R. colandina). The other new species is described from Apurímac and represents the first microendemic species of Ribes from this generally poorly explored region. It is a far southern outlier of the Ribes andicola group, which otherwise finds its southern range limit in the Department of La Libertad. Ribes apurimacensis differs from its closest allies in the Ribes andicola group by an exclusively glandular indument (no simple hairs) in combination with smaller leaves, a serrate leaf margin and dark red flowers.